2008
DOI: 10.1007/s11695-008-9717-2
|View full text |Cite
|
Sign up to set email alerts
|

The Utility of the Beck Depression Inventory in a Bariatric Surgery Population

Abstract: The BDI, with or without the somatic items, appears to be a reasonable screening measure for depressive symptoms among bariatric surgery candidates and the subpopulation of those with chronic pain, although future investigations may wish to examine whether other measures would have improved discrimination accuracy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 27 publications
3
29
0
1
Order By: Relevance
“…The sociodemographic results of our study are in line with the findings in earlier trials, that is, similar percentage of women (3/4 of the study population), median BMI and age [37,40,47,48]. Krukowski et al [37] found a similar BMI (49 kg/m 2 ) in predominantly female patients (84%) with a mean age of 43 years, but higher rates of minimal and mild depression in their investigation on the utility of Beck's Depression Inventory in bariatric patients. Cassin et al [40] found similar BMI (48 kg/m 2 ) and a mean age (44 years), as well as a high proportion of female gender (77%).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The sociodemographic results of our study are in line with the findings in earlier trials, that is, similar percentage of women (3/4 of the study population), median BMI and age [37,40,47,48]. Krukowski et al [37] found a similar BMI (49 kg/m 2 ) in predominantly female patients (84%) with a mean age of 43 years, but higher rates of minimal and mild depression in their investigation on the utility of Beck's Depression Inventory in bariatric patients. Cassin et al [40] found similar BMI (48 kg/m 2 ) and a mean age (44 years), as well as a high proportion of female gender (77%).…”
Section: Discussionsupporting
confidence: 91%
“…Cassin et al [40] found similar BMI (48 kg/m 2 ) and a mean age (44 years), as well as a high proportion of female gender (77%). The elevated proportion of female gender, associated with higher depression severity, has been shown in various studies [37,40,49,50] and could be confirmed in our analysis. However, BMI was not correlated to depression severity or somatization in our study.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The BDI is a 21-item scale and has been used already in bariatric surgery patient populations [20]. Individual items are rated from 0 to 3 to indicate severity and are summed to create a total score.…”
Section: Psychosocial Measuresmentioning
confidence: 99%
“…In addition, Krukowski et al [28] found that the BDI effectively predicted which obese individuals had depression. Furthermore, Castellini et al [29] demonstrated that the BDI had high prevalence rates when symptoms of depression and anxiety were present.…”
Section: Strength and Weakness In Relation To Other Studies And A Dismentioning
confidence: 99%